Methylation of NR3C1 is related to maternal PTSD, parenting stress and maternal medial prefrontal cortical activity in response to child separation among mothers with histories of violence exposure - Schechter, Daniel S.; Moser, Dominik A.; Paoloni-Giacobino, Ariane; Stenz, Ludwig; Gex-Fabry, Marianne; Aue, Tatjana; Adouan, Wafae; Cordero, María I.; Suardi, Francesca; Manini, Aurelia; Sancho Rossignol, Ana; Merminod, Gaëlle; et al. (Frontiers in Psychology, 2015)
Prior research has shown that mothers with Interpersonal Violence-related Posttraumatic Stress Disorder (IPV-PTSD) report greater difficulty in parenting their toddlers. Relative to their frequent early exposure to violence and maltreatment, these mothers display dysregulation of their hypothalamic pituitary adrenal axis (HPA-axis), characterized by hypocortisolism. Considering methylation of the promoter region of the glucocorticoid receptor gene NR3C1 as a marker for HPA-axis functioning, with less methylation likely being associated with less circulating cortisol, the present study tested the hypothesis that the degree of methylation of this gene would be negatively correlated with maternal IPV-PTSD severity and parenting stress, and positively correlated with medial prefrontal cortical (mPFC) activity in response to video-stimuli of stressful versus non-stressful mother-child interactions. Following a mental health assessment, 45 mothers and their children (ages 12-42 months) participated in a behavioral protocol involving free-play and laboratory stressors such as mother-child separation. Maternal DNA was extracted from saliva. Interactive behavior was rated on the CARE-Index. During subsequent fMRI scanning, mothers were shown films of free-play and separation drawn from this protocol. Maternal PTSD severity and parenting stress were negatively correlated with the mean percentage of methylation of NR3C1. Maternal mPFC activity in response to video-stimuli of mother-child separation versus play correlated positively to NR3C1 methylation, and negatively to maternal IPV-PTSD and parenting stress. Among interactive behavior variables, child cooperativeness in play was positively correlated with NR3C1 methylation. Thus, the present study is the first published report to our knowledge, suggesting convergence of behavioral, epigenetic, and neuroimaging data that form a psychobiological signature of parenting-risk in the context of early life stress and PTSD.